VD_FINDINFO HC / 2016 / 177 vom 19. Februar 2016 - VD Tribunal cantonal (2016)
TRANSACTIONACCORD, PROTECTION DE L'UNION CONJUGALE, FRAIS JUDICIAIRES | 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)